(3YhGed GdfLGM GdMQLI hJMbjb GdJejR aj GdCOGA GdeDSSjs - (3YeGO MeOj(B, (3YHO GdRYHjs ((3YeGf(B:s (3OGQ CeLO ddfTQ hGdJhRjY(B,s, 2022)
(3GdEWGQ GdYGe ddOQGSI, GdOQGSGJ GdSGHbI, GdEWGQ GdfXQj, YhGed GdfLGM GdMQLI, eaghegG, CgejJgG hahGFOgG, WQb JMOjO YhGed GdfLGM GdMQLI, CHYGO YhGed GdfLGM GdMQLI, OYe GdEOGQI GdYdjG, ESJQGJjLjI GdTQcI, KbGaI GdTQcI, JcfhdhLjG EOGQI GdeYQaI, GdJejR aj GdCOGA GdeDSSj, fTCJg, eagheg hCHYGOg, JWhjQ bOQGJ hegGQGJ GdehXajf, JYRjR GdbOQI GdJfGaSjI, LhOI GdefJLGJ, feGPL GdJejR, bWGY UfGYI GdCOhjI GdCQOfj, efgLjI JGdOQGSI, WHjYI GdHMK GdYdej aj eLGd GdCYeGd, fhY GdHMK, adSaI GdHMK, ZQV GdHMK, efgL GdHMK, GSJQGJjLjI GdHMK, LeY GdHjGfGJ hGdYjfGJ, eYjGQ hLhOI GdHMK, GdCSGdjH GdEMUGFjI GdeSJNOeI, GdJMdjd hGdfJGFL, hUa hNUGFU YjfI GdOQGSI MSH GdeJZjQGJ GdTNUjI hGdhXjajI, JMdjd CSFdI GdOQGSI, GNJHGQ GdJMbb ef edGAeI GdHjGfGJ ddJMdjd GdEMUGFj, GNJHGQ GdaQVjGJ, GdfJGFL hGdJhUjGJ(B.s
(3GdeQGLY U(B.241 (3GdedGMb U(B.260s
Keywords: (3GdCOGA GdeDSSjs; (3GdEOGQI(B- (3JWhjQs; (3GdJejRs; (3GdfLGM GdEOGQjs